Integrated Quality Management for the Existence of Pastoral Ministries at the Bethel Church of Indonesia Parakletos - Djone Georges Nicolas (Quantitative Economics and Management Studies, 2022)
The Covid-19 pandemic still ongoing today is a challenge and a struggle for every area of human life without exception. For example, business life is disrupted because of economic problems. Politically, the tension between one nation and another affects market prices and impacts basic needs and the sustainability of people's lives. Likewise, pastoral service activities have undergone a total change since the pandemic, resulting in some church services not functioning properly. For example, some worship services were shifted from building to house in a face-to-face to virtual style. This study aims to analyze the role of integrated quality management in the existence of pastoral ministry today, using a descriptive qualitative method approach with an Integrated Quality Management (MMT) system. The author collects data through observation, interviews, and literature documentation at the Bethel Church of Indonesia Parakletos Taman Palem Lestari, Cengkareng, West Jakarta. As a result, Integrated Quality Management is very important. It is a central need in customer satisfaction in this day and age, so church leaders must open up and realize that change is a certainty that not only has to be faced but will be better if anticipated by continuously innovating and creating in the grace of God.